The effect of explosive speed refinement on endurance development in senior football players: A field study on the Ahmed Loulou team – Souk Ahras - guessmi, Faycel; mahfoudi, Mahmoud (sports creativity, 2025)
The primary objective of our research is to investigate the potential impact of speed and explosive repetition on the development of specific endurance in football. We analyzed the results of the Mini Cooper test and reviewed 24 video interviews. Our key findings are: Specific endurance is developed through speed and explosive repetition, but there is a lack of consistency in ball touches at the end of the first and second halves.